The Age-IPV Curve: Changes in Intimate Partner Violence Perpetration during Adolescence and Young Adulthood - Johnson, Wendi L. (J Youth Adolesc, 2014)
Research on intimate partner violence (IPV) has evolved over the last decade with increasing interest in how IPV develops over adolescence and young adulthood. Studies examining patterns of IPV over time have generally focused on victimization with less attention to temporal shifts in perpetration. While it is generally assumed that IPV peaks during young adulthood, this has not been empirically verified and documented. Additionally, prior longitudinal analyses of IPV have focused on identifying trajectories and their accompanying risk factors, with less attention given to within-individual change in IPV experiences across and within relationships. Drawing on five waves of data from the Toledo Adolescent Relationships Study (TARS), we examined patterns of the perpetration of IPV among a diverse sample of adolescents and young adults (51.1% female, 63.9% non-Hispanic White, 24.6% non-Hispanic Black, 11.5% Hispanic) spanning the ages of 13–28 years (N = 1,164). Analyses demonstrated that IPV patterns deviate from the age-crime curve, with women’s involvement in IPV increasing, while their involvement in other antisocial behaviors is decreasing. Traditional behavioral and psychological risk factors (delinquency, alcohol and drug use, depressive symptoms) accounted for some of the age variation in IPV for men, but these factors did not account for age variation in IPV among women. Relationship risk factors including frequency of disagreements, trust, jealousy, validation and self-disclosure, however, accounted for substantial portions of the age-IPV perpetration relationship for male and female youth. These findings reinforce recent calls for prevention efforts that focus on the development and maintenance of healthy relationships.